Faktor-Faktor Yang Mempengaruhi Terjadinya Pernikahan Dini Pada Remaja di Dusun Sei Sembilang Kecamatan Banyuasin II Kabupaten Banyuasin Tahun 2025 - Nadia Septiani Rahma Tika; Ratna Dewi; Eka Rahmawati (JURNAL BIDANG ILMU KESEHATAN, 2026)
Early marriage remains one of the reproductive health issues as well as a social problem with a relatively high prevalence in Indonesia, including in Banyuasin Regency. According to BPS (2023) data, early marriage in Indonesia’s South Sumatra Province ranks second among five provinces, with a percentage of 11.41%. Initial data obtained through interviews with the Head of Dusun Sei Sembilang Village indicated that there were 60 adolescents in 2022, 50 adolescents in 2023, 63 adolescents in 2024, and 46 adolescents in the January–March 2025 period, showing a tendency for early marriage to increase.This study aims to examine the influence of education, knowledge, and family support on the occurrence of early marriage among adolescents. The study employed a quantitative analytic design with a cross-sectional approach. A total of 46 adolescents were sampled using total sampling technique. Data were analyzed using the Chi-Square test.The results showed a significant relationship between education (p=0.042), knowledge (p=0.000), and family support (p=0.000) with early marriage. The conclusion of this study is that low education, lack of knowledge about reproductive health, and high family support are dominant factors contributing to the occurrence of early marriage in Dusun Sei Sembilang. The study recommends the enhancement of reproductive health education programs, promotion of appropriate marriage age, and strengthening the role of families in providing positive support so that adolescents can postpone marriage until an ideal age